8-Shogaol inhibits rheumatoid arthritis through targeting TAK1. (April 2022) - Jo, Seongin; Samarpita, Snigdha; Lee, Ji Su; Lee, Yong Joon; Son, Joe Eun; Jeong, Minju; Kim, Jae Hwan; Hong, Seungpyo; Yoo, Seung-Ah; Kim, Wan-Uk; Rasool, Mahaboobkhan; Byun, Sanguine
Abstract: Rheumatoid arthritis (RA) is a chronic immune-mediated disorder, mainly characterized by synovial inflammation and joint damage. If insufficiently treated, RA can lead to irreversible joint destruction and decreased life expectancy. While better understanding of the pathologies and the development of new antirheumatic drugs have improved the outcome of individuals with RA, many patients still cannot achieve remission and experience progressive disability. Fibroblast-like synoviocytes (FLS) have gained attention due to its pivotal role in RA pathogenesis and thus targeting FLS has been suggested as an attractive therapeutic strategy. To identify candidate molecules with strong inhibitory activity against FLS inflammation, we tested the effect of 315 natural extracts against IL-17-mediated IL-6 production. Zingiber officinale was found as the top hit and further analysis on the active compound responsible led to the discovery of 8-shogaol as a potent molecule against synovitis. 8-Shogaol displayed significant inhibitory effects against TNF-α-, IL-1β-, and IL-17-mediated inflammation and migration in RA patient-derived FLS (RA-FLS) and 3D synovial culture system. 8-Shogaol selectively and directly inhibited TAK1 activity and subsequently suppressed IKK, Akt, and MAPK signaling pathways. Moreover, treatment with 8-shogaol reduced paw thickness and improved walking performance in the adjuvant-induced arthritic (AIA) rat model. 8-Shogaol also reversed pathologies of joint structure in AIA rats and decreased inflammatory biomarkers in the joints. Collectively, we report a novel natural compound that inhibits RA through reversing pathologies of the inflamed synovium via targeting TAK1. Graphical Abstract: ga1 Highlights: 8-Shogaol suppresses TNF-α-, IL-1β-, and IL-17-mediated inflammation and migration. 8-Shogaol directly inhibits TAK1 activity. 8-Shogaol inhibits rheumatoid arthritis in adjuvant-induced arthritic rats.